Análise da vida útil de lâmpadas fluorescentes utilizando diferentes tipos de circuitos de pré-aquecimento - Crepaldi, José Augusto (2012)
In the present days, the fluorescent lamps are being widely used. When compared to the incandescent normal lamps, due to its greater luminous efficiency, the use of fluorescent lamps results in considerable energy saving. However, the fluorescent lamps present some particularities. One important characteristic is the fact that, if the temperature of the filaments is not adequate at the ignition moment, it is necessary to apply a high tension to turn on the lamp. This tends to accelerate the lamp´s wear, reducing its lifetime. Therefore, the presence of an auxiliary preheating circuit for the fluorescent lamps, especially the T5 type, is fundamental to prevent its filaments from wearing out, guarantying a better condition for the ignition, and, consequently, resulting in a longer lifetime. This paper presents the main types of preheating circuits to self-oscillating ballast for T5 fluorescent lamps. This project proposes the development and implementation of an electronic system of autonomous tests, through which it is possible to perform a comparative test between the most common preheating types. Thus, this system of tests has to be able to evaluate the influence of these circuits in the fluorescent lamps´ lifetime, through the number of operation cycles accomplished until the lamps´ defects. Also, the test circuit has the incumbency of identifying the adequate operation of the preheating circuits, resulting in the study and possible implementation of needed modifications for the correct functioning of these circuits.